IMPROVEMENT OF DESCRIPTION TEXT WRITING SKILLS THROUGH THE APPLICATION OF THE CLUSTERING METHOD FOR STUDENTS - Tin Hadriani (Widyagogik, 2020)
Writing skill is a competency that the student should accive in the end of teaching and learning process, in each genre they learned. Description text is a texs that, learned in grade ten (x) in the first semester. Description text is text that decribe place, thing and people in detail. The structure text of description text are identification and description the language features of description text are. Use-present tense, noun phrase and passive sentence. In fact there are many student who cannot write the description text well. Their paragraph is bad, they use the wrong tense, diction and noun phrase. Their creativity is still low there is few students who answer and ask to the teacher, if they have problem and they are afraid to share their ideas so the researcher try to do the class action researh using clustering method to increase the students,  skill in writing description text : This class action researh is carried out in class X IPS 4 SMAN 1 Tengaran 2014/2015 academic year in first semester. Based on this class action research, using clustering method can increase students’ writing skill in writing description text